V.3 (New Haven, 1960)
In the tradition of the preceding volumes in this series, this volume reports a series of experimental studies independently conceived by different authors but bearing on a common theoretical issue. The focus here is on the internal structure of attitudes and on the relation among the affective, cognitive, and behavioral components of attitudinal structure. An issue dealt with in some way by all investigators concerns the consequences for attitude change of creating discrepancies between 2 components of attitudinal structure. 4 chapters are devoted to detailed exposition of experimental studies and discussions of their theoretical significance. In the final chapter, Hovland and Rosenberg provide a concise summary of the major findings and offer suggestions for future research.
Keywords: Attitude